A New Classification Approach of Cultural Heritage: Deep Learning Based Image Recognition - Atas, Serhat; Karakose, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2023)
With the development of technology, artificial intelligence is becoming gigantic and entering many areas. This development of artificial intelligence has also revealed beautiful studies by making contributions to the cultural heritage. These studies have shown that our cultural self and technology are actually not far from each other and are instrumental in useful studies. Many platforms have contributed to the development of various studies as a front for combining cultural heritage with developing artificial intelligence. In these various studies, not only artificial intelligence, but many different technologies have been used and tried to contribute to the cultural heritage. We have brought together deep learning and cultural heritage by deconstructing a study in this field. In our study, together with the special data set we have created, we have carried out a study that tries to recognize cultural heritage structures with deep learning by choosing a suitable model for our study, and we have described the contributions we have made in this study in this article. © 2023 IEEE.
2023 International Conference on Sustaining Heritage: Innovative and Digital Approaches, ICSH 2023 -- 18 June 2023 through 19 June 2023 -- Virtual, Online -- 198561
Keywords: cultural heritage; deep learning; image classification